2014
DOI: 10.1007/s11033-014-3047-3
|View full text |Cite
|
Sign up to set email alerts
|

Side populations from cervical-cancer-derived cell lines have stem-cell-like properties

Abstract: The target cells for the transforming mutations caused by high-risk human papillomavirus (HPV) infection could be the stem cells of the uterine cervical epithelium, generating particular cancer stem cells (CSCs). The aim of this study was to identify and characterize the CSCs from cervical-cancer-derived cell lines. The ability of SiHa, CaLo, and C-33A cell lines to efflux Hoechst 33342 was evaluated by flow cytometry and cells from the corresponding side populations (SPs) and nonside populations (NSPs) were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 59 publications
5
11
0
Order By: Relevance
“…We observed a much higher proportion of FTC-sensitive SP population mainly in HPV þ cells than the HPV À cells where the SP cells were barely detectable. This is in concordance with the earlier report (34). Furthermore, we observed that HPV þ SP cells effectively formed cervicospheres, a hallmark feature of stemness and self-renewal capacity (35) but HPV À SP cells (C33a) failed to form cervicospheres.…”
Section: Discussionsupporting
confidence: 93%
“…We observed a much higher proportion of FTC-sensitive SP population mainly in HPV þ cells than the HPV À cells where the SP cells were barely detectable. This is in concordance with the earlier report (34). Furthermore, we observed that HPV þ SP cells effectively formed cervicospheres, a hallmark feature of stemness and self-renewal capacity (35) but HPV À SP cells (C33a) failed to form cervicospheres.…”
Section: Discussionsupporting
confidence: 93%
“…The self-renewal capability observed in cells from the α6-integrin bri /CD71 dim subpopulation in HaCaT cells reported in this work, was similar to that reported in several works in the identification of both adult normal and cancer stem cells, where the isolated progenitor subpopulation was also able to reestablish the initial phenotype of the total population, increasing also the number of putative “progenitor” cells after each cycle of separation [46, 59, 60]. However, in a clear contrast with cancer stem cells, putative progenitor cell population in HaCaT was considerably lower and its enrichment after reseeding was not exponential.…”
Section: Discussionsupporting
confidence: 88%
“…This term emphasizes the absence of quiescence cells (stem) in proliferating cell lines. Villanueva and colaborators showed the presence of a G 0 subpopulation of cells (quiescence) in a side population derived from the HeLa cell line, additionally demonstrating their self-renewal capacity as shown by an increase in side population cells after serial sorting assays [10]. We must be careful to use the term cervical cancer stem cells (CCSC), however, since our spheres are cultured without fetal bovine serum (which contains differentiation stimuli) and we using a commercial medium for enriching stem cells with EGF and bFGF, thus, we suggest that our spheres are enriched for cervical tumorigenic cells and they could named cervical cancer stem cell-like cells, characterized by stemness and cervical stem markers.…”
Section: Discussionmentioning
confidence: 99%
“…However, because normal cervical epithelial stem cell markers remain unknown, general strategies are suggested to isolate CSC-enriched subsets and early progenitors, such as Side population (SP) and Aldehyde dehydrogenase activity (ALDH) assays. Villanueva and collaborators have reported the presence of a SP in SiHa and CaLo cervical cancer cell lines, in which these SP cells have shown properties of CSC, such as the capacity to form colonies in clonogenic assays [10]. In our group, HeLa SP and CD49f (α-integrin) cells were also evaluated in HeLa cervospheres [11].…”
Section: Introductionmentioning
confidence: 99%